Neuronal spoken word recognition: The time course of processing variation in the speech signal. - Schild, Ulrike; Röder, Brigitte; Friedrich, Claudia K. (Language & Cognitive Processes, 2012)
Recent neurobiological studies revealed evidence for lexical representations that are not specified for the coronal place of articulation (PLACE; Friedrich, Eulitz, & Lahiri, 2006; Friedrich, Lahiri, & Eulitz, 2008). Here we tested when these types of underspecified representations influence neuronal speech recognition. In a unimodal auditory–auditory word fragment priming experiment target words either had initial coronal PLACE (e.g., tiger) or had initial noncoronal PLACE (e.g., pony). Prime-target pairs were either identical (e.g., ti-tiger, po-pony), differed in initial PLACE (e.g., pi-tiger, to-pony), or were unrelated. Event-related Potentials for identical and related targets started to differ from unrelated targets at 100 ms, indicating early perceptual processing. Different effects for coronal vs. noncoronal variation were observed starting at 200 ms. Results are related to recent neurocognitive research on compensation for assimilation of PLACE (e.g., rainbow realised as *raimbow). A time line of processing PLACE variation at multiple stages is proposed and parallel processing of specified and underspecified representations at the lexical level is discussed.